Avaliação do impacto da capacitação profissional do servidor público municipal - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
Professional training is a powerful weapon in the quest for development of human skills in the workplace. The focus on training and development has become essential to achieve excellence in service delivery. In public administration,agencies responsible for professional development are the government schools, who work with public servants and employees in improving the state machine, which has the duty to provide quality public services to society. This study objective is to evaluate the impact of professional training of the server in the Manaus Prefecture and how this training affects their professional lives, analyzing also aspects related to organizational support provided to the server to develop quality skills acquired in training. The analysis was done by adapting the IMPACT model of evaluation of training by applying with public servants who took part in professional training activities promoted by the Public Service School of Manaus Prefecture (ESPI), comprising the dimensions Training Impact in Work, Organizational Support Training and Support Training Transfer. The results suggest that there is a strong positive impact of professional training administered by ESPI in work activities of the servers, however, the support given by the management to training requires adjustments to able to provide a better use of knowledge and skills acquired by servers in favor by your institutions.
Keywords: Capacitação profissional; Avaliação de treinamento; Servidor público; Prefeitura de Manaus; Professional training; Training evaluation; Public servant; Manaus Prefecture; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO